2020
DOI: 10.1684/ecn.2020.0456
|View full text |Cite
|
Sign up to set email alerts
|

Extensive longitudinal immune profiling reveals sustained innate immune activaton in COVID-19 patients with unfavorable outcome

Abstract: COVID-19 differs substantially between individuals, ranging from mild to severe or even fatal. Heterogeneity in the immune response against SARS-COV-2 likely contributes to this. Therefore, we explored the temporal dynamics of key cellular and soluble mediators of innate and adaptive immune activation in relation to COVID-19 severity and progression. Forty-four patients with a PCR-proven diagnosis of COVID-19 were included. Extensive cellular (leukocytes and T-lymphocyte subsets) and serological imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Flowcytometric leukocyte analysis and serological analysis of cytokines and soluble cell surface molecules have been reported previously by Schrijver et al [31]. All assays were performed according to manufacturer's protocol.…”
Section: Haematological and Serological Analysismentioning
confidence: 99%
“…Flowcytometric leukocyte analysis and serological analysis of cytokines and soluble cell surface molecules have been reported previously by Schrijver et al [31]. All assays were performed according to manufacturer's protocol.…”
Section: Haematological and Serological Analysismentioning
confidence: 99%
“…COVID‐19 patients have been reported to consistently generate a substantial Tlymphocyte response against antigens derived from various SARS‐CoV‐2 proteins 5 . Nevertheless, evidence of immune dysregulation in COVID‐19 is accumulating, including reduced peripheral T‐lymphocyte numbers, an exaggerated and/or prolonged inflammatory response, and T‐lymphocytes displaying characteristics of exhaustion 6,7,8 . The complexity of the growing evidence underlines the importance of the cellular immune response in COVID‐19, alongside the established role of the humoral response 9,10,11,12 …”
Section: Introductionmentioning
confidence: 99%
“…reduced peripheral T-lymphocyte numbers, an exaggerated and/or prolonged inflammatory response, and T-lymphocytes displaying characteristics of exhaustion. 6,7,8 The complexity of the growing evidence underlines the importance of the cellular immune response in COVID-19, alongside the established role of the humoral response. 9,10,11,12 The T-cell receptor beta (TRB) repertoire is tremendously diverse.…”
mentioning
confidence: 99%
“…Because the systematic evaluation of DNA methylation signature of COVID-19 in relation to the biological age is currently a new scientific inquiry [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , this correspondence is organized around three overarching medico-legal concerns that need to be addressed for understanding the influence of COVID-19 on forensic age estimation in survivors. These concerns include: (1) the possibilities of biological and/or epigenetic age acceleration [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , TL attrition [17] , [24] , [35] , [36] , and altered thymic function with its closely related marker (sjTrec) that may be involved in the pathogenesis of COVID-19 [30] , [31] , [32] , [33] , [34] ; (2) the presence of population differences in both vulnerability and the outcome of the infection such as mortality and long COVID syndrome which has ramifications on the precision of age estimates by the forensic models [37] , [38] , [39] , [40] , [41] ; (3) the protective effect exerted by mRNA vaccines and drugs like metformin, rapamycin, and anti-androgens as potential lifespan-extending against COVID-19 and subsequently the deceleration of epigenetic age [21] , [42] , [43] .…”
mentioning
confidence: 99%
“…Therefore, obvious cell-type shifts in the composition of blood cell have been correlated with the severity of COVID-19 disease due to the effect of COVID-19 DNAm signature. For example, a low count of lymphocytes (particularly, the CD4+ and CD8+) and decreased production of naïve T-cells are implicated in the prediction and prognosis of severe COVID-19 [31] , [32] , [33] . Pang et al [21] observed increasing CD4+ Naïve T cells in COVID-19 patients under 50 years of age.…”
mentioning
confidence: 99%